Challenges of moving into Medium Density Walk-up Residential Flats (MDWRFs): a case of Harare - Manyunzu, David Chinamasa (My University, 2022)
There has been an increase in the number of developments in medium density walk-up residential flats (MDWRFs) in Harare in the last decade and current policies are increasingly inclined towards multi-storey housing. The Zimbabwe National Human Settlements Policy of 2019 put a 40% minimum threshold of multi-storey housing in every housing project because of the benefits of this form of housing. However, multi-storey housing does not come without its challenges particularly to low-income residents. This study investigates the challenges that are faced with residents when transitioning into medium density walk-up residential flats with particular focus on livelihoods and assets, habitability and management of common spaces and facilities. In doing so, the study fills a research gap of scarcity in studies of MDWRFs in Zimbabwe and present recommendations for future planning and design of this form of housing. The mixed methods research approach which combine open ended and closed ended questions in a single questionnaire survey is adopted. The study explores the residential environment using the experience and evaluation of the residents which in a way also reveals the strengths and weaknesses of the current form of MDWRFs. The study found out that the satisfaction level with the current form of MDWRFs is high and the major weaknesses that need to be improved on are alternatives to municipal water, communal spaces in building, maintenance of communal facilities, private outdoor spaces, local public facilities, fire safety, public security in neighbourhood and green areas and landscape.
A research report submitted to the Faculty of Engineering and Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Urban Studiesin the field of Housing and Human Settlements, 2022